In vivo double-strand breaks occur at recombinogenic G + C-rich sequences in the yeast mitochondrial genome. - Zinn, A R (1988)
An optional 46-base-pair G + C-rich element (GC cluster) in the coding region of the yeast mitochondrial var1 gene inserts preferentially in crosses into recipient alleles that lack the sequence. Unlike a similar gene conversion event involving the insertion of an optional 1143-base-pair intron, the mitochondrial 21S rRNA gene, which requires the action of a protein encoded by a gene within that intron, conversion of the var1 GC cluster does not require any protein product of the mitochondrial genome. We have detected double-strand breaks in the var1 gene in mitochondrial DNA isolated from unmated haploid rho+ and rho- strains at or near the boundaries of the optional GC cluster, as well as at a conserved copy of that sequence 160 base pairs upstream. No double-strand breaks were detected in the recipient var1 DNA molecules in the vicinity of the optional GC cluster target sequence. This contrasts with 21S rRNA-encoding DNA (rDNA) intron conversion where the recipient, but not the donor DNA, is cleaved at the element insertion site. These results suggest that although the 21S rDNA intron and the var1 GC cluster are preferentially inserted into their respective short alleles, these conversions probably occur by different mechanisms.